The serum metabolome mediates the concert of diet, exercise, and neurogenesis, determining the risk for cognitive decline and dementia. Issue 4 (17th August 2021) - Du Preez, Andrea; Lefèvre‐Arbogast, Sophie; Houghton, Vikki; de Lucia, Chiara; Low, Dorrain Y.; Helmer, Catherine; Féart, Catherine; Delcourt, Cécile; Proust‐Lima, Cécile; Pallàs, Mercè; Ruigrok, Silvie R.; Altendorfer, Barbara; et al.
Abstract: Introduction: Diet and exercise influence the risk of cognitive decline (CD) and dementia through the food metabolome and exercise‐triggered endogenous factors, which use the blood as a vehicle to communicate with the brain. These factors might act in concert with hippocampal neurogenesis (HN) to shape CD and dementia. Methods: Using an in vitro neurogenesis assay, we examined the effects of serum samples from a longitudinal cohort (n = 418) on proxy HN readouts and their association with future CD and dementia across a 12‐year period. Results: Altered apoptosis and reduced hippocampal progenitor cell integrity were associated with exercise and diet and predicted subsequent CD and dementia. The effects of exercise and diet on CD specifically were mediated by apoptosis. Discussion: Diet and exercise might influence neurogenesis long before the onset of CD and dementia. Alterations in HN could signify the start of the pathological process and potentially represent biomarkers for CD and dementia.